Evaluation of ovarian reserve with amh level in patients with well-differentiated thyroid cancer receiving radioactive iodine ablation treatment - Acıbucu, Fettah; Acıbucu Oğuz, Duygu; Akkar Bozoklu, Özlem; Dökmetaş, Hatice Sebila (Johann Ambrosius Barth Verlag Medizinverlage Heidelberg Gmbh, 2016)
Introduction: Radioactive iodine (RAI) ablation treatment is used for patients diagnosed with well-differentiated thyroid cancer in order to reduce the risk of recurrence. RAI ablation treatment can adversely affect gonads in males and females. In this study, we aimed to determine ovary damage and infertility risk due to RAI, using serum anti-Mullerian hormone (AMH) level, in females who received RAI ablation treatment. Materials and Methods: 45 female patients who have not gone through the menopause and had received RAI ablation treatment for well-differentiated thyroid cancer in premenopausal period, and 40 healthy females as control groups were included in this study. The serum AMH, follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), thyroid stimulating hormone (TSH) and creatinine levels of the patients included in the study were analyzed and compared to those of the control group with similar demographical characteristics. Results: No differences were found between the patient group and control group in terms of age, height, weight, body mass index, LH, E2 and creatinine. The difference in AMH, FSH and TSH between both groups were found to be significant. There was no statistically significant relation between the age and AMH levels. Similarly, no statistically significant relation between RAI exposure duration and AMH levels was determined. When the patients below and above the age of 35 were compared with regard to AMH (2.95 +/- 1.79 and 2.75 +/- 1.94, respectively) and FSH (5.45 +/- 1.63 and 5.99 +/- 3.06, respectively), the difference between them was found to be statistically insignificant. Oligo/anovulation was detected in 7 patients (15.6 % of the patient group) after RAI treatment, 8 (17.8 %) patients became pregnant after RAI treatment, and none of the patients, who were actively trying to get pregnant, were unable to achieve it. Conclusion: According to these results, it may be concluded that low AMH levels due to RAI treatment can cause damage to the ovaries of patients; nevertheless, considering the AMH levels and the absence of infertility in the patients, the infertility risk was found to be low.
WOS: 000390416900003
PubMed ID: 27711957
Keywords: Anti-Mullerian Hormone; Radioactive Iodine; Thyroid Cancer